Pelatihan Komunikasi Efektif Bagi Perangkat dan Lembaga Desa Untuk Meningkatkan Kualitas Pelayanan Publik - Handayani, Rindu; Maulana, Said Akhmad (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2026)
Village officials often work based on their individual experiences without systematic guidelines on how to communicate effectively in serving the community, resulting in service inconsistencies that impact dissatisfaction and a decline in the quality of public services. This community service activity aimed to improve the effective communication skills of village officials and village institutions in order to enhance the quality of public services in Sarangmandi Village. The activity involved 20 participants, consisting of village officials and institutions (village office staff, the head of the PKK, neighborhood heads (RT), and the head of the Youth Organization/Karang Taruna), as well as university students conducting their Community Service Program (KKN) in Sarangmandi Village. The training was carried out through presentations and practical sessions on effective communication, emphasizing speaking techniques, body language, and public speaking skills in the context of public service. The results of the activity indicate that participants were able to apply more structured and confident communication, and became more responsive to community needs in the service process